Longeyes
Reputation
329
Next privilege 500 Rep.
Access review queues
 Apr 6 awarded Popular Question Mar 29 revised show $\sum_{j=0}^n (-1)^j {n \brack j}_q =0$ for n odd added 10 characters in body; edited tags Mar 29 asked show $\sum_{j=0}^n (-1)^j {n \brack j}_q =0$ for n odd Mar 9 accepted Number of Plane Oriented Recursive Trees Mar 9 comment Number of Plane Oriented Recursive Trees Aaah! Well that makes me feel a lot better, thank you!! Mar 9 asked Number of Plane Oriented Recursive Trees Aug 14 asked How to find the period of a recurrence relation Jul 6 accepted Find order of elliptic curve Jul 6 asked Find order of elliptic curve Jun 26 awarded Yearling Jun 26 accepted Factor RSA number $n$. Jun 26 revised Factor RSA number $n$. edited body Jun 26 revised Factor RSA number $n$. edited body Jun 26 asked Factor RSA number $n$. Feb 1 awarded Talkative Feb 1 comment How to work with a statement: “for all $x$, if $p(x)$ then $q(x)$” (contradiction and contraposition) Feb 1 comment How to work with a statement: “for all $x$, if $p(x)$ then $q(x)$” (contradiction and contraposition) The tautologies (K.0)-(K.1) on this sheet might be useful to you: math.ethz.ch/~halorenz/4students/logikGT/Tautologien.pdf Feb 1 comment How to work with a statement: “for all $x$, if $p(x)$ then $q(x)$” (contradiction and contraposition) No, $\forall x(p(x) \rightarrow q(x))$ is equivalent to $\forall x:(\lnot p(x) \lor q(x))$ That's right, we leave the outer quantifier be. Feb 1 comment How to work with a statement: “for all $x$, if $p(x)$ then $q(x)$” (contradiction and contraposition) Because $p \rightarrow q$ is logically equivalent to $\lnot p \lor q$. Since $\lnot q \rightarrow \lnot p$ is the contraposition of $p \rightarrow q$ your statement is equivalent to $\forall x:(\lnot q(x) \rightarrow \lnot p(x))$ Feb 1 awarded Teacher